Hubungan Antara Kadar Hemoglobin (Hb) Dengan Prestasi Belajar Siswa Mi Muhammadiyah Program Khusus Kecamatan Kartasura Kabupaten Sukoharjo - Perdana, Irfan Halim, dr. Mohammad Shoim Dasuki, M.Kes, dr. Anika Candrasari, M.Kes (2015)
Background: The learning achievement is the result or the level of capability that has been achieved by students after joining the learning process in a certain time. The highly learning achievement is not only influenced by the intelligence, but also other factors, one is anemia. It can decrease person's ability to work and all population with the serious economic consequences for the nation development. Anemia can cause the reduction of person's thinking and concentration, decrease the learning achievement of students as having difficulty concentrating. The purpose of this study wa to identify and analyze the correlation among hemoglobin levels to the student achievement. Method: This research is an analytic observational using cross sectional approach. The sampling in this research uses random sampling with the number of 40 students in MI Muhammadiyah Program Khusus Kartasura. This research uses Che-Square test. Result: Hemoglobin levels and the Learning Achievement of Student MI Muhmmadiyah Program Khusus Kartasura obtained by Che-Square test is p > 0.05, means there is no significant correlation statistically. Conclusion: There is no correlation between the hemoglobin level and the learning achievement of student MI Muhammadiyah Program Khusus Kartasura.